The Crucible of Conscience: Morality and Spirituality in Military Service - Rolland, Rakotonindriana David; Baholy, Robijaona Rahelivololoniaina (Budapest International Research and Critics University, 2025)
On the one hand, discipline is the main strength of the military. On the other hand, without discipline, there is total anarchy within the military compound. But on the other hand, without God, the army works in vain. A soldier is first of all a man or a woman, that is to say a human body, endowed with a body, a soul and a spirit. The three work in harmony. This is what differentiates man from animal and other creatures of God. These are the ideas on which this article is based. The army will always be close to God, even considered as the third institution of God. It’s been talked about a lot, and it’s written from beginning to end in the Bible. It even looks like it’s God’s temple. This article presents a Christian perspective of soldiers, preparing them for non-traditional ministry, training them to make the profession of faith. The key is to bring the gospel of Jesus Christ to every uniformed man and woman in the military, and then spread the gospel through the military chaplaincy to the military families. The ministry among the military is biblical. Is this call to chaplaincy the biblical basis of military profession, in order to prepare soldiers spiritually?